The Effect of Two Acute Bouts of Exercise on Oxidative Stress, Hematological, and Biochemical Parameters, and Rectal Temperature in Trained Canicross Dogs - Erjavec, Vladimira; Vovk, Tomaž; Nemec Svete, Alenka (Frontiers in Veterinary Science, 2022)
Canicross is a sport discipline that connects human and canine athletes in running. Changes in physiological, hematological, and biochemical parameters, and exercise-induced oxidative stress have not been thoroughly characterized in canicross dogs. The aim of our study was the assessment of the health status of trained canicross dogs that were subjected to two acute bouts of exercise with their owners during the training season. Health status was assessed by measuring the rectal temperature, hematological and biochemical parameters, as well as blood oxidative stress parameters (plasma malondialdehyde, lipid peroxidation marker; whole blood glutathione peroxidase and erythrocyte superoxide dismutase1, antioxidant enzymes) before and during a two-day canicross training session and after a 24-hour rest period. Seven trained canicross dogs (3 females/4 males) aged 12 to 120 months were included in the study. Blood samples were collected before and immediately after the first acute bout of exercise (day 1), after the second acute bout of exercise (day 2), and after 24 hours of rest (day 3). Rectal temperature was measured at the same time as blood sample collection. The majority of hematological and biochemical parameters remained within reference ranges at all sampling times. Rectal temperature was significantly higher after training on days 1 and 2 compared to resting temperature on day 3. Hematological parameters did not change significantly; however, there were significant differences in urea, creatinine, creatine kinase, and triglycerides between specific sampling times. Despite significant changes, these biochemical parameters remained within reference ranges. Significant changes in biochemical parameters seem to reflect the dogs’ physiological response to each acute bout of exercise, considering all biochemical parameters and rectal temperature returned to pre-exercise values after a 24-hour recovery period (day 3). No significant differences in oxidative stress parameters were found between any sampling times. Relatively high erythrocyte superoxide dismutase1 activity at all sampling times may indicate that the canicross dogs are adapted to training by an increased expression of antioxidant enzymes. Based on our results, we can conclude that the trained canicross dogs included in our study were healthy, in good physical condition, and fit for the two acute bouts of field exercise.